Creative Thinking Skills in Museum Context and Guidelines to Build a Creative practice - Carvalho, Ana (2020)
Creative thinking is likely to be one of the essential skills for the 21st Century, not just for museum professionals but also for professionals across all areas of our society. As society changes, an array of new technologies and practices emerge, which require flexibility and improvisation from museums and museum professionals. Creative thinking is one of the skills that are crucial to adapt and respond more effectively to changing realities, whether in digital or non-digital environments. This learning object focus on the value of creative thinking skills to help museum professionals enhance their creative potential and, thus, build a practice that supports the museum mission, and introduces 11 guidelines to start building a creative practice. This learning object is part of the module “Creative Thinking Skills” of the MOOC “Essential Digital Skills for Museum Professionals” developed by Project Mu.SA – Museum Sector Alliance (575907-EEP-1-2016-1-EL-EPPKA2-SSA). This learning object was also produced as a narrated video at: https://youtu.be/ZVh9l5bGSD0